Screendance Self/portraits - Blades, Hetty (The International Journal of Screendance, 2017)
Screendance works often comprise multiple authorial perspectives. The camera, staging, sound, choreography and context all contribute to the aesthetic and conceptual potential of the work. This provocation draws on Tamara Tomić-Vajagić’s (2016) notion of the ‘self-portrait effect’ to discuss how a confluence of first and third person perspectives cultivates representations of selfhood in two screendance examples: Vis-er-al (2015) by Polly Hudson and 52 Portraits (2016) by Jonathan Burrows, Matteo Fargion, and Hugo Glendinning.